FGN 46 Neurospora Bibliography - Craig Wilson (Fungal Genetics Reports, 1999)
This bibliography represents my attempt to collect all works dealing substantially with Neurospora. Please let me know of anything published in 1998 or 1999 that is not included here, so that it might be mentioned in the next bibliography.